MANAGEMENT CONTROL SYSTEMS AS A MODERATOR OF THE LOW-COST STRATEGY–PERFORMANCE RELATIONSHIP: AN EMPIRICAL STUDY FROM PADANG CITY, INDONESIA - Imaniar; Arisa Darlin; Zaitul (POLITEKNIK LP3I JAKARTA, 2026)
This study examines the impact of a low-cost strategy on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Padang City, Indonesia, and explores whether Management Control Systems (MCS) moderate this relationship. MSMEs are critical to Indonesia’s economic growth, employment, and poverty reduction, yet face challenges from increased competition, technological change, and economic uncertainty. Adopting appropriate strategies, such as a low-cost approach, is essential for sustaining performance, though prior research on its effectiveness has yielded mixed results. Furthermore, the role of MCS in enhancing strategy implementation, especially in emerging economies, remains underexplored. Using a quantitative approach, survey data were collected from fourteen MSME owners and analysed with Partial Least Squares Structural Equation Modelling (PLS-SEM). Results reveal that the low-cost strategy significantly improves enterprise performance (β = 0.449; p = 0.099), while MCS on their own do does not have a significant effect (β = 0.498; p = 0.143). Additionally, MCS do not significantly moderate the link between low-cost strategy and performance (β = –0.111; p = 0.626). The model explains a substantial proportion of variance in enterprise performance (R² = 0.809) and demonstrates strong predictive relevance (Q² = 0.610). These findings contribute to the contingency theory by showing that formal management control practices alone are not sufficient to enhance strategic effectiveness in MSMEs unless they are consistently implemented and aligned with organizational characteristics. The study offers practical insights for policymakers and MSME owners seeking to improve strategic management in emerging markets.